O31 Explaining ethnic variations in sti diagnosis: results from britain's third national survey of sexual attitudes and lifestyles (NATSAL-3). (8th June 2017) - Wayal, Sonali; Hughes, Gwenda; Sonnenberg, Pam; Mohammed, Hamish; Gerressu, Makeda; Furegato, Martina; Mercer, Catherine
Abstract : Introduction: In Britain, ethnic inequalities in STIs diagnoses persist. We hypothesised that these inequalities are associated with variations in sexual behaviour, which are influenced by differences in socioeconomic deprivation (SED) and mediated by substance use. Methods: Data from 14, 563 participants of Britain's third National Survey of Sexual Attitudes and Lifestyles, a probability sample survey (N=15, 162), were analysed by gender and ethnicity: white British (WB, reference category), black Caribbean (BC), black African (BA), Indian, Pakistani, white other (WO), and mixed ethnicity (ME). Using multivariable regression we examined ethnic variations in reported STI diagnoses adjusted for age, partner numbers (last 5y), recreational drug use (last 1y), and SED, and calculated adjusted odds ratios (AOR). Results: SED was higher in BC, BA, and Pakistani participants than other ethnicities (50% vs. 16%-38%, p<0.0001). compared with men from other ethnicities, BC and BA men reported higher partner numbers (p<0.0001), and concurrent partnerships (27% and 39% respectively vs. 4%–15%, p=0.001). compared with women from other ethnicities, ME women reported higher partner numbers (p<0.0001) and concurrency (14% vs. 2%–8%, p=0.0005). Recreational drug use was highest among WO and ME participants (26% vs. 4%-15% among other ethnicities; p<0.0001). Reported STI diagnosis was highest among BC men (8.7) and ME women (6.7%), and remained AOR high after adjustment for BC men (2.68, 95%CI: 1.13–6.34) and ME women (2.03, 95%CI: 1.11–3.68). Discussion: Ethnic variations in sexual behaviours, mediators, and SED partially explain higher STI diagnoses among BC men and ME women highlighting need for holistic interventions addressing these broader determinants.